Dividend Payout Ratio and Investor Behavior in Shariah-Compliant Firms: The Case of PT. Semen Indonesia - Adiwiguna, Muhamad Yuga Prawira (Journal of Economicate Studies, 2019)
This study investigates the impact of the Dividend Payout Ratio (DPR) on investor interest in PT. Semen Indonesia, a leading state-owned firm listed in the Jakarta Islamic Index. Using a qualitative method, the study analyzes how dividend consistency influences investor confidence in Shariah-compliant environments. The findings demonstrate that DPR serves as both a financial signal and an ethical indicator, particularly valued by Muslim investors who prioritize al-amanah and al-maslahah. Internally, profitability and retained earnings shape dividend decisions, while externally, state ownership and Islamic financial regulations set expectations for ethical conduct. The research concludes that optimizing DPR requires balancing financial performance with religious values. This study contributes to both corporate finance and Islamic economics by proposing a framework that harmonizes dividend policy with maqāṣid al-sharīʿah, offering practical strategies for corporate managers and regulators in Islamic markets.